2016
DOI: 10.1080/00981389.2016.1231744
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of change: Conceptualizing the social work response to LGBTQ microaggressions in health settings

Abstract: Despite the emergence of research on microaggressions targeting lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) communities in recent years, there remains an insufficiency of theoretical literature in this area. In this article, we draw on the works of Michel Foucault to conceptualize the effects of microaggressive practices on LGBTQ people accessing health and other social services, and generate insight into strategies these groups use to resist these effects. We emphasize the need for soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As social workers, we can work for additional funding, increased program creation, and additional communication between supports and service users. Kia, 2016) have found that service users experience numerous micro-aggressions when accessing healthcare, in addition to systemic barriers. These micro-aggressions consist of;…”
Section: The Role Of Social Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…As social workers, we can work for additional funding, increased program creation, and additional communication between supports and service users. Kia, 2016) have found that service users experience numerous micro-aggressions when accessing healthcare, in addition to systemic barriers. These micro-aggressions consist of;…”
Section: The Role Of Social Workersmentioning
confidence: 99%
“…In response to these micro-aggressions Kia et al (2016) have made several recommendations for social workers to consider when working with LGBTQ2S+ service users.…”
Section: Nadal Et Al (2010 As Cited Inmentioning
confidence: 99%
“…Advocacy is generally considered to be a core aspect of the social work identity and it takes on particular resonance in a hospital context where patients may be frail and vulnerable, may not have relatives or friends to act in their interests, or may be faced with life-changing decisions (Sexton, 2012). The importance of advocacy in hospital social work with older people has been highlighted in a number of studies (Craig and Lorenzo, 2014; Findley, 2015; Kia et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In defining micaroaggression, Solorzano et al (2000) identified it as the restrained insults (verbal, non-verbal or visual) directed at people of colour, often routinely or unconsciously. Disappointedly, this issue of microaggressions is often overlooked in research, shown in only five studies on microaggression (Otuyelu et al (2016), Kia et al (2016), Caragata and Liegghio (2013), Baden (2016), and Wong and Jones (2018). Specifically, little attention was paid to microaggression among social work professionals, students and education settings (Wong & Jones, 2018); it is an under-investigated research area.…”
Section: Introductionmentioning
confidence: 99%